Analysis of Environmental Risk Factors for Leprosy in Indonesian Society: Meta-Analysis - Guguk Fadjari Ari Edi; R Azizah (Poltekkes Kemenkes Palu, 2023)
Indonesia is still the third largest contributor of new cases of leprosy in the world. The purpose of this study was to analyze the risk factors for the influence of humidity, occupancy density, and personal hygiene on the incidence of leprosy. Using the Meta-Analytic Method with the PICOS technique. Some of the data sources used are Google Scholar, Research Gate and Plos ONE by looking at keywords such as